Delayed Patch-Test Reading After 5 Days: An Update From the Mayo Clinic Contact Dermatitis Group. Issue 4 (July 2017) - Chaudhry, Hafsa M.; Drage, Lisa A.; El-Azhary, Rokea A.; Hall, Matthew R.; Killian, Jill M.; Prakash, Amy V.; Yiannias, James A.; Davis, Mark D.P.
Abstract : Background: Patch-test readings after day 5 have previously been used to identify delayed reactions to metals and topical antibiotics. Objective: The aims of this study were to identify allergens for which late readings (beyond day 5) would be most valuable and to compare our results with our previous study on delayed patch-test readings. Methods: This was a retrospective study of 298 patients who underwent metal and corticosteroid series patch testing from January 1, 2007, through December 31, 2013. Patch-test readings were conducted on days 3 and 5 and at least once sometime between days 7 and 14. All reactions were examined at each reading. Conclusions: These results were concordant with our previous findings that additional readings after day 7 are particularly useful for identifying reactions to metals (gold, cobalt, beryllium, palladium), specific preservatives (dodecyl gallate, propolis), and the topical antibiotic neomycin. New delayed reactions to bacitracin, p -phenylenediamine, and topical corticosteroids were not seen in this cohort.